Changes in health-related quality of life during transition to adult healthcare: an international prospective cohort study - Kallio, Mira Marianne (BMJ Publishing Group, 2025)
OBJECTIVE: To study changes in health-related quality of life (HRQoL) in adolescents and young adults (AYAs) with chronic medical conditions across the transfer to adult healthcare and associations of HRQoL with transition readiness and experience of care.
METHODS: Participants in this international (Finland, Australia) prospective cohort study were recruited in the year prior to transfer to adult health services and studied 12 months later. In addition to two HRQoL scales (Pediatric Quality of Life inventory (PedsQL), 16D), the Am I ON TRAC for Adult Care Questionnaire and Adolescent Friendly Hospital Survey measured transition readiness and experience of care and categorised by quartile. Data were compared before and after transfer to adult healthcare.
RESULTS: In total, 512 AYAs completed the first survey (0-12 months before transfer of care) and 336 AYAs completed it 1 year later (retention rate 66%, mean ages 17.8 and 18.9 years, respectively). Mean total PedsQL scores (76.5 vs 78.3) showed no significant change, although the social and educational subdomains improved after transfer of care. The mean single-index 16D score remained the same, but in Finland, distress increased and the ability to interact with friends decreased after transfer. AYAs within the best quartiles of experience of care and transition readiness had better HRQoL than AYAs within the worst quartiles.
CONCLUSIONS: Overall HRQoL of AYAs remained unchanged across the transfer to adult healthcare. Recognising and supporting AYAs with unsatisfactory experience of care and poor transition readiness could improve overall HRQoL during the transition process.\nNCT04631965.